HOW E-WALLET USAGE TRIGGERS IMPULSIVE BUYING IN ONLINE LIVE SHOPPING PLATFORM: EVIDENCE FROM INDONESIA - Sudhian Aryadipura; Muhammad Fikrinala Margaliu; Miranda Tanjung (Faculty of Economics and Business Udayana University, 2025)
The study examines factors influencing impulsive buying in live shopping, focusing on e-wallet usage, hedonic motives, perceived risk, and celebrity endorsers. Using a quantitative, explanatory research, data were collected in 2024 from 349 respondents who had used live shopping features on Shopee, TikTok Shop, or Lazada with e-wallets in the last six months. Data analysis employed Structural Equation Modeling (SEM-PLS). Six hypotheses were tested, and results indicate that e-wallet usage positively influences impulsive buying, while hedonic motives mediate this effect. Celebrity endorsers strengthen the relationship between hedonic motives and impulsive buying, but perceived risk does not moderate the link between e-wallet usage and impulsive buying. However, perceived risk does not impact the relationship. The findings suggest that e-commerce platforms should leverage live shopping and celebrity endorsements to boost sales. Future research should explore additional moderators (e.g., cultural factors, interfaces) and longitudinal impacts of impulsive buying behavior in live commerce contexts.